School Discipline as a Consequence of Violent Victimization in Adolescence: Understanding the Mediating Roles of Head Injury and Behavior - Loomis, Alysse M. (Journal of interpersonal violence, 2022)
Pathways from violence to head injury and poor long-term outcomes have been found among numerous populations, however, have not yet been widely examined with youth exposed to violence. Traumatic brain injuries (TBIs) are linked to a range of consequences salient to adolescent development and well-being, such as impulsivity, academic abilities, and emotional processing. This gap in research has led to a missed opportunity to understand the consequences of youth victimization, particularly within the academic setting. The current study examined whether head injury and problem behaviors mediate the relationships between victimization and suspension/expulsion using data from the Pathways to Desistance Study, a multi-site, longitudinal study of serious adolescent offenders age 14?18. A sample of male youth who had witnessed violence (n = 1,094) reported a total score of victimization, number of early behavior problems (i.e., cheating, fighting, etc.), ever having a head injury (32.9%), and number of times suspended (adjusted M = 13.13; SD = 19.31) or expelled (adjusted M = 0.65; SD = 0.99). Structural equation modeling was used to examine direct and indirect pathways from victimization to suspension and expulsion through head injury and behavior. Direct pathways from victimization to school discipline were significant; indirect pathways mediated by only head injury were not significant, but indirect pathways through only problem behavior and through TBI and problem behavior were significant for both expulsion and suspension. Results suggest that youth who have been victimized are at higher risk for both suspension and expulsion and that this risk may be, in part, explained through increased head injury and problem behaviors. TBI screenings/services for violence-exposed youth and trauma-informed school-based services may help to deter trajectories toward suspension and expulsion but should be developed with attention to the influence of racial bias on pathways to school discipline.